Bacterial Carbonic Anhydrases as Drug Targets: Toward Novel Antibiotics? - Supuran, Claudiu T. (Frontiers in Pharmacology, 2011)
Carbonic anhydrases (CAs, EC 4.2.1.1) are metalloenzymes which catalyze the hydration of carbon dioxide to bicarbonate and protons. Many pathogenic bacteria encode such enzymes belonging to the a-, b-, and/or g-CA families. In the last decade, the a-CAs from Neisseria spp. and Helicobacter pylori as well as the b-class enzymes from Escherichia coli, H. pylori, Mycobacterium tuberculosis, Brucella spp., Streptococcus pneumoniae, Salmonella enterica and Haemophilus influenzae have been cloned and characterized in detail. For some of these enzymes the X-ray crystal structures were determined, and in vitro and in vivo inhibition studies with various classes of inhibitors, such as anions, sulfonamides and sulfamates reported. Although efficient inhibitors have been reported for many such enzymes, only for Nessseria spp., H. pylori, B. suis and S. pneumoniae enzymes it has been possible to evidence inhibition of bacterial growth in vivo. Thus, bacterial CAs represent promising targets for obtaining antibacterials devoid of the resistance problems of the clinically used such agents but further studies are needed to validate these and other less investigated enzymes as novel drug targets